KONSTITUSIONALITAS JABATAN WAKIL MENTERI PERSPEKTIF SIYASAH DUSTURIYAH - Firmansyah; Samin, Sabri; Mustarin, Basyirah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
The appointment of deputy ministers is the president's prerogative which aims to assist ministers in carrying out ministerial affairs in certain ministries. This study aims to find out how urgent the appointment of deputy ministers in Indonesia is and how the legitimacy of the appointment of deputy ministers is in the view of siyasa dusturiyah. The problem in this research is in Article 10 of law number 39 of 2008 concerning state ministries as the legality of appointing deputy ministers in the phrase "special handling" in the article does not explain clearly and in detail how special handling is meant, so this can be it has the potential to just divide up positions, because we know the position of deputy minister is a political position. This research is a library research with a juridical and normative syar'i approach. Sources of primary and secondary data are literature such as: the 1945 Constitution, decisions, the Koran, scientific works, legal academics, legal dictionaries, opinions, magazines. The results of this study are 1) The urgency of appointing deputy ministers by the president is to assist several ministers who have a greater workload in certain ministries. 2) The position of the deputy minister in the Indonesian constitution is as a body that assists the ministry, even though the position of deputy minister is not regulated in the 1945 Constitution does not mean it is prohibited, from a substance standpoint there is no constitutionality problem in this situation because of the general principle in law "something that is not commanded and not prohibited it may be done ". 3) The validity of the appointment of deputy ministers in the view of siyasa dusturiyah lies in the authority to appoint/give positions by the head of state or caliph who both have prerogative rights, and there are similarities in the criteria for requirements to become a deputy minister.